A Smart IOT Approach to Optimize Electric Circuit Breaker Reliability and Functionality - Solly Aryza; Zulkarnain Lubis; Khairil Putra (Sean Institute, 2025)
In modern electric power systems, circuit breakers play a critical role in maintaining operational safety and system stability by disconnecting faulty sections during abnormal conditions. However, the reliability and functionality of conventional circuit breakers are often compromised due to delayed maintenance, undetected mechanical wear, and the lack of real-time monitoring. This study proposes a smart Internet of Things (IOT)-based approach to enhance the reliability and functionality of electric circuit breakers by enabling real-time data acquisition, condition monitoring, and predictive maintenance. The system integrates various sensors—such as temperature, current, and vibration sensors—connected through microcontrollers and cloud platforms for remote access and analysis. Through simulations and prototype testing, the proposed system demonstrates improved response time in fault detection, early failure diagnosis, and efficient maintenance scheduling. This research highlights the potential of IOT technology in transforming traditional power protection systems into intelligent, adaptive, and more reliable infrastructures.